SOSIALISASI PEMANFAATAN IT UNTUK MENINGKATAN TATA KELOLA ADMINISTRASI PEMERINTAHAN DESA DI PEKON PANDANSARI SELATAN - Elisabet Yunaeti Anggareni; Sucipto Sucipto; Suyono Suyono (Jurnal PkM Pemberdayaan Masyarakat, 2021)
Indonesia is a country that has many islands and diverse cultures. From one area to another, they have different customs. But we often see that in one area there are many social stratifications that occur. Because they have different social developments, cities and villages are formed. The ability of the village to manage governance, implementation, community development and community empowerment must be supported by all village elements and resources to support the improvement of the welfare of the village community. A village that can carry out development management independently is not only able to mobilize all resource assets owned by the village, but the village will also be able to improve the basic needs of residents, livelihood needs, fight for community rights and organize life in a sustainable manner. One of the resources that can be utilized by the village is the use of Information and Communication Technology, the development of science and technology cannot be separated from the development of human needs. One of the information technology that is developing rapidly is technology using application media and the internet that can be accessed anywhere, so that data entry can be done from anywhere and can be controlled from one place as a central. From this, as modern humans are required to change the way in managing the village by utilizing IT from various fields, one of which is in the scope of the field of village government in Pekon Pandansari Selatan